Bio-Oil: The Next-Generation Source of Chemicals - Henrique Machado; Ana F. Cristino; Sofia Orišková; Rui Galhano dos Santos (Reactions, 2022)
Bio-oil, although rich in chemical species, is primarily used as fuel oil, due to its greater calorific power when compared to the biomass from which it is made. The incomplete understanding of how to explore its chemical potential as a source of value-added chemicals and, therefore, a supply of intermediary chemical species is due to the diverse composition of bio-oil. Being biomass-based, making it subject to composition changes, bio-oil is obtained via different processes, the two most common being fast pyrolysis and hydrothermal liquefaction. Different methods result in different bio-oil compositions even from the same original biomass. Understanding which biomass source and process results in a particular chemical makeup is of interest to those concerned with the refinement or direct application in chemical reactions of bio-oil. This paper presents a summary of published bio-oil production methods, origin biomass, and the resulting composition.